Akomodasi Komunikasi Imakes Dalam Interaksi Antarbudaya (Studi Deskriptif Kualitatif Akomodasi Anggota Ikatan Mahasiswa Asal Kebumen yang Berada di Solo) - Azmah, Roifah Dzatu; , Ratri Kusumaningtyas, M.Si (2017)
The difference culture are generally not eassy to accepted in the society, the exsistence old culture that makes of the other culture are different. Lack ability to understand by society in variety of cutures makes some problem in their communication. Stereotypes, the immigrants have to adapted to a new culture for example, a student from kebumen who migrated to Solo. There are different cultures between both of the Solo and Kebumen. The researcher observes the process accommodation of the student by identity the culture is about the language of ngapak. This study used a qualitative approach with a phenomenological method. Results of Accommodation communication in intercultural interaction on students from Kebumen is they indicate a modification of the language when interacting with other students. Moreover, they also use the approach flight in intercultural communication. There is nothing while adjustments communication barriers experienced in intercultural interaction of Kebumen student.